PENGARUH MEDIA SOSIAL TIKTOK TERHADAP PERILAKU KONSUMTIF MAHASISWA (STUDI KASUS : MAHASISWA PENDIDIKAN ANTROPOLOGI) - Zendrato, Indah Natalia; Daniel Harapan Parlindungan Simanjuntak (JURNAL PENDIDIKAN IPS, 2025)
The purpose of this study is to find out the Influence of TikTok Social Media on the Consumptive Behavior of Anthropology Education Students, Faculty of Social Sciences, State University of Medan. This type of research is quantitative. The population in this study is Anthropology Education Students class of 2021 with a sample of 100 students based on the calculation of the Slovin formula. The data collection method uses a questionnaire and the data analysis method uses simple linear regression and hypothesis testing. The results of the study showed that TikTok social media had a significant effect on consumptive behavior. In the hypothesis test, a significance value of 0.000 < 0.05 or a t-value of 3.805 > t table 1.984 was obtained, which means that Ho was rejected and Ha was accepted. So it can be concluded that there is an influence of TikTok social media on students' consumptive behavior